Factors associated with overweight and childhood obesity in Spain according to the latest national health survey (2011) - Maria Julia Ajejas Bazán; Maria del Carmen Sellán Soto; Antonio Vázquez Sellán; Maria Luisa Díaz Martínez; Silvia Domínguez Fernández (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To describe the factors associated with overweight/obesity in Spain according to the latest National Health Survey (2011). Method: Descriptive cross-sectional study with 3,752 children aged 2 to 15 years (boys=2,007; girls=1,745). Main variables: overweight; obesity; gender; level of education of the head of the family; monthly income; hours of sleep; physical exercise; hours of TV and/or computer use; daily breakfast; parents' weight perception. Diagnostic criterion was based on WHO growth patterns, defined overweight with +1SD and obesity, +2SD. Results: Boys more obese than girls. Children whose parents had a lower level of education, those who did not practice physical activity and whose parents had an income of less than 900€ per month showed a higher percentage of overweight/obesity. Conclusions: Children whose parents had a lower education and monthly income presented a higher percentage of obesity. Sleeping the recommended hours and doing some type of physical activity reduces obesity.